Transfusion of Uncrossmatched Group O Erythrocyte-containing Products Does Not Interfere with Most ABO Typings. (March 2020) - Yazer, Mark H.; Spinella, Philip C.; Doyle, Leilani; Kaufman, Richard M.; Dunn, Robyn; Hess, John R.; Filho, Luiz Amorim; Fontaine, Magali; Gathof, Birgit; Jackson, Bryon; Murphy, Michael F.; Pasion, Jeremiah; et al.
Abstract : Background: Group O erythrocytes and/or whole blood are used for urgent transfusions in patients of unknown blood type. This study investigated the impact of transfusing increasing numbers of uncrossmatched type O products on the recipient's first in-hospital ABO type. Methods: This was a retrospective cohort study. Results of the first ABO type obtained in adult, non–type O recipients ( i.e., types A, B, AB) after receiving at least one unit of uncrossmatched type O erythrocyte-containing product(s) for any bleeding etiology were analyzed along with the number of uncrossmatched type O erythrocyte-containing products administered in the prehospital and/or in hospital setting before the first type and screen sample was drawn. Results: There were 10 institutions that contributed a total of 695 patient records. Among patients who received up to 10 uncrossmatched type O erythrocyte-containing products, the median A antigen agglutination strength in A and AB individuals on forward typing ( i.e., testing the recipient's erythrocytes for A and/or B antigens) was the maximum (4+), whereas the median B antigen agglutination strength among B and AB recipients of up to 10 units was 3 to 4+. The median agglutination strength on the reverse type ( i.e., testing the recipient's plasma for corresponding anti-A and -B antibodies) was very strong, between 3 and 4+, for recipients of up to 10 units of uncrossmatched erythrocyte-containing products. Overall, the ABO type of 665 of 695 (95.7%; 95% CI, 93.9 to 97.0%) of these patients could be accurately determined on the first type and screen sample obtained after transfusion of uncrossmatched type O erythrocyte-containing products. Conclusions: The transfusion of smaller quantities of uncrossmatched type O erythrocyte-containing products, in particular up to 10 units, does not usually interfere with determining the recipient's ABO type. The early collection of a type and screen sample is important. Abstract : ABO typing in 665 of 695 (95.7%) non–group O recipients could be accurately determined on the first type and screen sample obtained by the blood bank after the transfusion of uncrossmatched type O erythrocyte-containing products.